PENDAMPINGAN DAN KAJI TERAP BIOBRIKET KULIT BIJI JAMBU METE DI DUSUN NGAGLIK DESA NGEPOSARI, KECAMATAN SEMANU KABUPATEN GUNUNGKIDUL - Wuye Ria Andayanie (Universitas Merdeka Madiun, 2022)
One of the ways to reduce oil consumption and land use is to use cashew nut processing waste to produce biocharcoal briquettes, which are made from cashew nut shells. The business potential of cashew nuts (Anacardium occidentale) in Ngaglik Hamlet, Ngeposari Village, Semanu District has prospects as a cashew nut producing area in Gunung Kidul Regency. Cashew nut shells contain fuel with high calorific value and long burning time and are safe for health. However, cashew shell waste has not been managed optimally. The purpose of this service program is to manage cashew nut shell waste as an alternative solid fuel product that can be used by the community as renewable energy. Lecture and discussion methods as well as question and answer are used for training. The contribution of this activity to society through technology transfer produces biobriquettes as a renewable and environmentally friendly energy. The application of science and technology biobriquettes from cashew nut shells has been adopted by cooperator farmers. This is shown by the results of the evaluation that 100% of the farmers made biobriquettes using the tools available in farmer groups for their own needs or for sale. The success of the application of science and technology was due to the transfer of technology from universities and the participation of cooperative and non-cooperative farmers from Ngaglik Hamlet, Ngeposari Village, Semanu District, Gunungkidul Regency, which went well.